Risk Factors for Postoperative Complications after Percutaneous Nephrolithotomy - Basnet, Robin Bahadur; Shrestha, Anil; Shrestha, Parash Mani; Joshi, Bishwa Raj (Journal of Nepal Health Research Council, 2018)
Background: To identify the perioperative factors associated with complications after percutaneous nephrolithotomy by classification of complications according to the modified Clavien scoring system and evaluation of the minor and major complications related to the procedure.Methods: A prospective study of all the percutaneous nephrolithotomy performed by standard technique within 1.5 years at Bir Hospital was made. Possible demographic, preoperative and intraoperative variables were included in the study and patients were followed up postoperatively for any complications. All complications were classified according to modified Clavien scoring system and analyzed to identify the prognostic variables.Results: Two hundred and forty six percutaneous nephrolithotomy done within the study period were analyzed. Although 41.06 % of the study population developed complications, only 9.35 % had major complications. Age, body mass index, gender, clinical presentation, history of previous surgery and ASA score did not correlate with complications. Diabetes was the only comorbidity associated (p = 0.0482). Preoperatively estimated stone burden (p = 0.0023), number of calyces involved by the stones (p = 0.0002), and presence of staghorn calculi were significantly associated with development of postoperative complications. Multiple tracts were required (p = 0.0151) and operative time was longer (p < 0001) in the patients who developed complications.Conclusions: Percutaneous nephrolithotomy has lesser complications. Diabetic patients are more prone to develop complications. Larger stone burden, involvement of multiple calyces by stones and staghorn calculi are associated with need of multiple tracts and longer operative time, thus predisposing to higher incidence of complications.